THE DIGITAL CULINARY CHAIN: BRAND AWARENESS’S CONTRIBUTORY ROLE FOR CONTENT MARKETING’S CONVERSION POWER - Joesran, Jessenia Odelia; Cantika, Diva; Hamdani, Felicia; Tunggala, Karenina; Erwin, Erwin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The rapid growth of the culinary industry increases competition, forcing businesses to follow new trends. Social media platforms have become an essential tool for creating marketing content that captures consumer attention and drives purchase intention. This research examines the effect of marketing content on purchase intention, with brand awareness as a mediating variable. The data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS. The study collected data from 205 respondents through questionnaires using a five-point Likert scale. The results indicate that marketing content has a positive influence on purchase intention. Furthermore, brand awareness was found to mediate the relationship between marketing content and purchase intention, suggesting that marketing content indirectly impacts consumers’ purchase intentions. These findings highlight the importance for culinary business owners to develop and manage relevant and appealing content to increase purchase intention. Moreover, well-designed marketing content plays a crucial role in enhancing brand awareness, which ultimately leads to higher consumer purchase intention.